ANALISIS PENGENDALIAN KUALITAS PRODUK DENGAN STATISTICAL QUALITY CONTROL (SQC) PADA PT EVERAGE VALVES METALS CABANG LAMONGAN - Bayu Sentosa; Nawari Nawari; Sa’abdillah Abas (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2021)
This study aims to determine the types of damage, the factors that cause damage, and whether product quality control at PT. Ever Age Valves Metals Lamongan Branch is still within the limits of control or not. Data collection techniques was done by direct observation and interviews. In the data processing of this research used the Statistical Quality Control (SQC) methods, those are checking sheets, pareto diagrams, cause and effect diagrams, and control charts . The results of this study indicated that the types of damage are boncel body, tepos body, body hole, porous body, broken handlebar, and broken hat. From the causal diagram it could be seen the factors that cause damage, namely humans, raw materials, methods, and tools. On the using of the p control chart showed that the product quality control process had still in the outside of control limit because there are still 7 points that are outside the quality control limit, those are in March, April, June, July, August, September, and November, thus it showed that the control process of product quality had not been implemented well.